A STUDY ON IMPACT OF ICT ON THE MARKETING STRATEGY OF INDIAN TOURISM INDUSTRY - Ansari, Md. Kashif; Jain, Garima; Kaur, Jasleen (International Journal of Research -GRANTHAALAYAH, 2017)
Deployment of ICT has been changing the way companies in every industry conduct their business. The most impacted is the marketing department. Marketers need to constantly study the market and the rapid changes in technology to continue satisfying the new-age customers. These customers have access to multiple sources of information due to increased usage of ICT. The present study analyses the evolution of Indian tourism industry, focusing on its marketing strategies over the years. The author reviews various sources to study the disruption caused by deployment of ICT in the marketing strategies used by the industry. Tourism industry is a combination of various interrelated industries, such as food industry, transport industry, hotel industry, etc. It was found that the information and communication technologies have revived the Indian tourism industry like never before. The impact can be noted in the form of price competition, changes in consumer behaviour, demand for customization, reduced barriers to entry and increased bargaining power of buyers.